(3TQM JMaI TGgOjs - (3eLghds ((3CMeO YdGFjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj QcH JaGYjd CHGOGffG hHYO adeG cGfJ JMaI TGgOj Ydjg QMeI GdgGOj eJOGhdI Hjf GdeMUdjf heWdhHI YfO GdeHJOFjf hcGfJ eTJedI Ydi HMhQ eNJdaI MGd chf CSeGFgG hCSeGA CLRGFgG HMSH RMGaGJgG aEfgG ecJhHI aj GHJOGA cd bWYI hcGf cKjQ ef WGdHjgG dG jSJcTs
(3BNQgG (B:s
(3hEfj bO HjfJ cd hGMO ef Jdc GdCSeGA hGdRNGQa Ke GP LGA eKdg KGfjI abO CMdJ Ydi HjGf eG SHb hHGdENJUGQ hEYJeGOkG Ydi aWGfI GdeJYdejf Ke HqjfJ eG CMdfG Ydi GdSGHb aj GdMGTjI HfGA Ydi QYGjI GdCPgGf GdaGfjI adjcf gPG BNQ eG ChQOfGs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdYQhV hGdbhGajs